1995
DOI: 10.1093/hmg/4.12.2227
|View full text |Cite
|
Sign up to set email alerts
|

Non-disjunction in human sperm: evidence for an effect of increasing paternal age

Abstract: In humans, the relationship between advancing maternal age and the incidence of trisomy has been long established, but the possible effect of increasing age of the father remains controversial. Using a fluorescence in situ hybridization (FISH) approach to directly examine individual sperm for aneuploidy of the sex chromosomes and chromosome 18, we have analyzed approximately 400,000 sperm from 24 men aged 18-60 years. There was no obvious relationship between increasing age and disomy 18, but the incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
134
5
7

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(161 citation statements)
references
References 0 publications
15
134
5
7
Order By: Relevance
“…We did not observe tetraploid sperm nuclei. Our results show rather large interindividual differences in diploidy frequencies, but the mean frequency (0.15%) is close to that reported by other groups (3,7,14,(21)(22)(23). Nine fertile men studied using probes for chromosomes 17 and 18 showed a frequency of 0.18% diploid spermatozoa (14), while another study among 10 normal donors showed higher frequencies of diploidy: 0.34% by using autosomal probes and 0.45% by using sex chromosome probes (7).…”
Section: Discussionsupporting
confidence: 86%
“…We did not observe tetraploid sperm nuclei. Our results show rather large interindividual differences in diploidy frequencies, but the mean frequency (0.15%) is close to that reported by other groups (3,7,14,(21)(22)(23). Nine fertile men studied using probes for chromosomes 17 and 18 showed a frequency of 0.18% diploid spermatozoa (14), while another study among 10 normal donors showed higher frequencies of diploidy: 0.34% by using autosomal probes and 0.45% by using sex chromosome probes (7).…”
Section: Discussionsupporting
confidence: 86%
“…Using a triple color FISH X-Y-8, we did not find a paternal age effect on sex chromosomes disomy (XX, YY, XY) in infertile patients and in donors. Our results are in accordance with the data of Bosch et al [39,40] and Luetjens et al [16], but in discordance with others studies which found an effect of age on the production of disomic sex chromosomes with varying results for XX, YY, XY [41][42][43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 84%
“…The rates of XX-and YY-sperm in this study reflect a combination of disomy resulting from meiosis II error and diploidy. Thus, the XX-and YY-sperm frequencies (0.28% and 0.27%) estimated in this study are higher than those reported previously (Wyrobek et al, 1990;Robbins et al, 1993;Griffin et aL, 1995) (Table 5). The rates of XX-and YY-diploid sperm are needed to calculate the true rates of disomy for sex chromosomes.…”
Section: Discussioncontrasting
confidence: 63%
“…The disomy rate (0.39%) for chromosome 17 in this study is comparable to those (0.33% and 0.31%) by Han et al (1992) and by Guttenbach et aL (1994a), while higher than that (0.13%) in the report of Bischoff et al (1994) (Table 5). The disomy rate (0.33%) obtained for chromosome 18 is comparable to those (0.36% and 0.25%) by Guttenbach et al (1994b) and by Bischoff et aL (1994), while higher than that Williams et al (1993) and by Griffin et al (1995) (Table 5). On the contrary, the diploidy rate in this study is comparable to those of other investigators (Han et al, 1992;Williams et aL, 1993;Miharu et aL, i994) (Table 5).…”
Section: Discussionmentioning
confidence: 48%